The Influence of Memorable Nature-Based Tourism Experiences on Environmentally Responsible Behavioral Intentions: An Environmental Education Perspective - aini nurhasanah; Ahmad Hudaiby Galih Kusumah (Al-Qalam Institue, 2026)
The growth of nature-based tourism raises environmental concerns if not accompanied by responsible tourist behavior. This study aims to analyze the effect of memorable nature-based tourism experiences on connectedness to nature and tourist satisfaction, and their implications for environmental awareness and environmentally responsible behavioral intentions, from an environmental education perspective. A quantitative explanatory design was employed, with data collected through a survey using questionnaires distributed to tourists selected through purposive sampling. Data were analyzed using Structural Equation Modeling (SEM). The results indicate that memorable naturebased tourism experiences have a positive and significant effect on both connectedness to nature and tourist satisfaction. Furthermore, these variables positively influence environmental awareness, which emerges as the strongest predictor of environmentally responsible behavioral intentions. These findings highlight the role of tourism experiences as a form of experiential environmental education that shapes tourists’ awareness and behavior. The study implies that destination managers should integrate environmental education strategies into tourism management by designing meaningful experiences that foster learning, awareness, and pro-environmental behavior. Such an approach strengthens the role of tourism as an educational medium for sustainability.